19F NMR Spectroscopy as a Highly Sensitive Method for the Direct Monitoring of Confined Crystallization within Nanoporous Materials. Issue 31 (7th June 2016) - Nartowski, Karol P.; Malhotra, Diksha; Hawarden, Lucy E.; Sibik, Juraj; Iuga, Dinu; Zeitler, J. Axel; Fábián, László; Khimyak, Yaroslav Z.
Abstract: The introduction of fluorine into the structure of pharmaceuticals has been an effective strategy for tuning their pharmacodynamic properties, with more than 40 new drugs entering the market in the last 15 years. In this context, 19 F NMR spectroscopy can be viewed as a useful method for investigating the host–guest chemistry of pharmaceuticals in nanosized drug‐delivery systems. Although the interest in confined crystallization, nanosized devices, and porous catalysts is gradually increasing, understanding of the complex phase behavior of organic molecules confined within nanochambers or nanoreactors is still lacking. Using 19 F magic‐angle‐spinning NMR spectroscopy, we obtained detailed mechanistic insight into the crystallization of flufenamic acid (FFA) in a confined environment of mesoporous silica materials with different pore diameters (3.2–29 nm), providing direct experimental evidence for the formation of a molecular‐liquid‐like layer besides crystalline confined FFA form I. Abstract : Detailed mechanistic insight into the crystallization of flufenamic acid (FFA) in the confined environment of mesoporous silica materials with different pore diameters (3.2–29 nm) was obtained by 19 F magic‐angle‐spinning NMR spectroscopy. This approach provided direct experimental evidence for the formation of a molecular‐liquid‐like layer besides crystalline confined FFA form I.